PENAGIHAN UTANG PAJAK MELALUI SURAT PAKSA ATAS HARTA KEKAYAAN PENANGGUNG PAJAK YANG TERSIMPAN DI BANK OLEH KANTOR PELAYANAN PAJAK PRATAMA PADANG DUA - Ashfihani Basnur; Yuslim Yuslim; Khairani Khairani (LPPM Universitas Ekasakti Padang, 2023)
The confiscation of the assets of the Taxpayer has been regulated in the Tax Collection Law with a Forced Letter. There are many tax arrears and additional debt by taxpayers every year with the realization of the disbursement of tax arrears that is not balanced with the number of existing tax arrears. The problems that occurred at KPP Pratama Padang Dua had not fully complied with the procedures and provisions of the General Tax Provisions Law and the Law on Tax Collection by Forced Letter. The main problem in this research is how is the implementation of collecting tax debts with a forced letter and what is the mechanism for using the assets of the tax bearer stored in the bank as a debt settlement. This legal research uses an empirical juridical approach, namely a research that uses an approach to the problem by looking at the applicable legal norms and then connecting it with the legal facts contained in the field. While this type of research is descriptive analytical. Data collection techniques were carried out through structured interviews and document studies. The results of the research implementation of the collection of tax debts with forced letters are first, basically tax collection is carried out if the tax bearer does not pay off the tax debt and tax collection fees, second, against the tax bearer who does not pay off the tax debt, officials can take action to collect taxes, third, implementation Tax Collection stages are carried out in accordance with statutory provisions in the field of Tax Collection with Distress Warrants, fourth, the implementation of Tax Collection stages is carried out against Tax Bearers by considering the order of priority. However, the priority is the significant value of the tax debt. The problems that occurred at KPP Pratama Padang Dua had not fully complied with the provisions of the KUP Law and the PPSP Law. And the mechanism for using the taxpayer's assets stored in the bank as a debt settlement, namely when a forced letter has been issued, at least 2x24 hours directly block the account, the way the KPP writes to the destination bank, then the bank blocks it, the bailiff (tax officer) will meet the taxpayer to discuss how payment will be made, if the taxpayer will pay off with money in a blocked account before 14 days, then the officer makes a billing and Minutes of Overbooking and an unblocking letter but if more than 14 days there is no response from the taxpayer, then the Officer can can directly transfer to the tax payable. However, in this case KPP Pratama Padang Dua has not fully implemented it for tax arrears whose accounts have been blocked. The settlement of tax debts with the assets of the taxpayers stored in the bank has been carried out by KPP Pratama Padang Dua, although it has been successfully implemented, it has not yet achieved maximum results in disbursing tax arrears.